Self-initiated expatriation (SIE) by older women: an exploratory study. Issue 2 (12th June 2017) - Myers, Barbara; Inkson, Kerr; Pringle, Judith K.
Abstract : Purpose: The purpose of this paper is to explore the SIE experiences of women over 50, its drivers, nature and outcomes. Design/methodology/approach: The paper draws on participant data from in-depth life story interviews with 21 women who had undertaken SIE from New Zealand and later returned. From this sample two subgroups (aid volunteers and contract carers) are utilized as "vignette" exemplars, and common factors elicited. Findings: SIE provided a desirable liberation from pressing mid-life issues. It was transformational for all participants, sometimes through serendipitous career development, but more commonly, after return, through personal development, changes in values, decreased emphasis on paid work, and simpler lifestyle. Research limitations/implications: The small sample size and qualitative methodology make the study exploratory rather than definitive and the specific location and small sample size limit transferability. The snowballing recruitment method may have disproportionately encouraged similar, and positively disposed, participants. Practical implications: The availability and special characteristics of this expatriate and repatriate group for potential employing organizations are considered, as are the gains in human capital and individual well-being to society as a whole. The women studied provide excellent role models for older women considering independent overseas travel and employment. Originality/value: By focusing on older women, this study extends the boundaries of the SIE literature. The findings highlight the limitations of work-centric theories of SIE, careers and older workers, the non-linear nature of women's careers and the heterogeneity of later life pathways. The study is also original in demonstrating major positive transformational effects of expatriation on all its participants.